2006
DOI: 10.1111/j.1083-6101.1999.tb00098.x
|View full text |Cite
|
Sign up to set email alerts
|

Educational Applications of CMCS: Solving Case Studies through Asynchronous Learning Networks

Abstract: Case studies are an important component of many business curricula. However, in‐class discussion of case studies suffers from temporal and geographical limitations. Computer‐mediated communication systems (CMCS) can be used to overcome these constraints. An Asynchronous Learning Network, a CMCS supporting “anytime/anywhere” interaction and tailored for educational activities, may be used to expand and enrich case discussions. ALN‐mediated discussions allow students and instructors from remote locations to part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 31 publications
0
30
0
Order By: Relevance
“…One alternative to provide a space for students is to integrate computer-mediated communication (CMC) tools that allow students to communicate asynchronously and provide this important interaction among students (Benbunan-Fich & Hiltz, 1999;Rourke & Anderson, 2002). Recent studies have shown the relevance of video communication using tools such as VoiceThread to support communication and social presence among students in distance environments (Borup, West & Graham, 2013;Ching & Hsu, 2013).…”
Section: Small Group Activities In Online Environmentsmentioning
confidence: 99%
“…One alternative to provide a space for students is to integrate computer-mediated communication (CMC) tools that allow students to communicate asynchronously and provide this important interaction among students (Benbunan-Fich & Hiltz, 1999;Rourke & Anderson, 2002). Recent studies have shown the relevance of video communication using tools such as VoiceThread to support communication and social presence among students in distance environments (Borup, West & Graham, 2013;Ching & Hsu, 2013).…”
Section: Small Group Activities In Online Environmentsmentioning
confidence: 99%
“…Since the research activities discussed in this paper were aimed at trying to characterize the group dynamics within distributed software teams, the researchers chose a coding scheme that tries to characterize student group's collaborative behaviors [32]. Curtis and Lawson [32] identify nine different behaviors (described in Johnson & Johnson [33]) as being supportive of the collaborative process, and then developed a coding schema that could be used to categorize different utterances in on-line collaboration.…”
Section: Data Analysis Proceduresmentioning
confidence: 99%
“…The original Curtis/Lawson [32] coding scheme was based on an exploratory study that examined online discussions of students who were engaged in a collaborative task. The authors examined the log files of interactions that occurred while using an online discussion management system.…”
Section: Social Interactionmentioning
confidence: 99%
“…E-learning library services have also been tackled by many scholars and researchers in recent years. Benbunan-Fich and Hiltz (1999) have critically discussed the use of computer-mediated communication systems (CMCS) in distance education; they also have focused on the convergence of technological and institutional factors involved in the promotion of e-learning. Jorgensen (2002) has highlighted the overall evolution and significance of the asynchronous learning network, and explored how online courses can be used to foster a rich collaborative e-learning environment and virtual classroom, whereas Cannon (2002) has outlined the potential catalytic role of the digital library in supporting the e-learning process.…”
Section: Related Literaturesmentioning
confidence: 99%